Panen Air Hujan Sebagai Sumber Air Bersih Alternatif di Wilayah DAS Bekasi Hulu - Evantri, Dea; M. Yanuar Jawardi Purwanto; Roh Santoso Budi Waspodo; Pandjaitan, Nora Herdiana (Jurnal Keteknikan Pertanian, 2021)
Rainwater harvesting is one of the efforts to reduce surface runoff and increase water availability. Rainwater harvesting becomes one of the alternatives to meet the water needs of the community and reduce the use of PDAM water or groundwater. Rainwater harvesting planning in the Bekasi watershed aims to meet the water needs of the community in the upstream areas of the Bekasi river who have used PDAM water. Rainwater harvest planning is calculated based on the amount of water needed and the accommodated rainwater volume. The dimension of the reservoir was planned with a capacity of 4 m³ with a height of 160 cm and a thickness of 3 cm. The result of the calculation of the water needs of the community in the Bekasi watershed in 2018 was 73 million m³/year or equivalent to Rp 110 billion in PDAM rates. Through the rainwater harvesting planning, the amount of rainwater collected each year reached 7.8 million m³/year. Based on this research, the community can save water costs by 11% of the total costs incurred for PDAM water costs. Rainwater harvesting can be applied in the Bekasi watershed in the upstream areas and it is time to socialize it to the community.